ANALISIS KEBUTUHAN SISWA TERHADAP PEMBELAJARAN BERBICARA BERBASIS TEORI KOGNITIF SOSIAL DI SEKOLAH MENENGAH ATAS - Safrihady, Safrihady; Suwandi, Sarwiji; Setiawan, Budhi; Rohmadi, Muhammad (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2023)
One of the main concerns of most language teachers is to provide solutions for language learners in order to develop language proficiency. In this case, speaking skills have become a major concern of language teachers as well as language learners. These problems in this research include the learning atmosphere that is not yet pleasant, the application of learning models and methods is not yet effective and efficient, students' internal constraints, the assessment process is not yet effective, and there is no motivation and involvement of all students' senses in learning. This study examines students' needs for learning to speak based on social cognitive theory. Data were obtained from class XI students in five senior high schools. The results of the research found that 1) it is necessary to create a pleasant learning atmosphere; 2) the need to choose the right model and method as well as apply it effectively and efficiently in learning because this is related to students' internal problems; 3) There needs to be an improvement process in aspects of the appraisal process; 4) there needs to be motivation and involvement of all student senses in learning. It can be concluded that this problem requires innovation and development of speaking teaching models in order to improve the quality of teaching speaking in class XI senior high school students.